(untitled) (Asian-Australasian Journal of Food Safety and Security, 2017)
The study was carried out from November, 2014 to February, 2015 with the objective of isolating Aeromonas hydrophila an important fish pathogen from infected air-breathing catfish Magur (Clarias batrachus) in Mymensingh district. Quantitative study of the isolated bacteria from infected C. batrachus was found variation of number in different organs. Total bacterial load was found to be 1.16 x 105 to 3.15 x 106 cfu/g in lesions, 2.14 x 108 to 4.17 x 109 cfu/g in liver, 1.90 x 107 to 5.12 x 108 cfu/g in spleen and 2.32 x 106 to 5.24 x 108 cfu/g in kidney of infected C. batrachus in Mymensingh district. The isolates were found to produce acid from arabinose, whereas acid and gas from different sugar media such as maltose, sucrose, and dextrose. Morover, they were capable to ferment glucose but resistant to vibriostatic agent 0129 test. Further identification of A. hydrophila was accomplished using PCR. The PCR products of desired 760 bp were obtained for A. hydrophila. The isolated A. hydrophila were 96% sensitive to Enrofloxacin followed by 88% to Ciprofloxacin and 76% to Levofloxacin. On the other way, 100% were resistant to the Ampicillin followed by 96% to Penicillin and 92% to Novobiocin. So far, this is the first molecular identification of A. hydrophila from farmed C. batrachus in Bangladesh. The present study will provide future research scopes on identification of pathogenicity island in chromosome and serotyping of all A. hydrophila isolates. Asian Australas. J. Food Saf. Secur. 2017, 1 (1), 17-24